2016
DOI: 10.1053/j.semnuclmed.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to Thyroid Cancer Treatment and Response Assessment

Abstract: The incidence of thyroid cancer has been on the rise. After total thyroidectomy of well differentiated thyroid tumors with intermediate or high-risk features on pathology, radioiodine remains one of the mainstays as the standard therapy for thyroid remnant ablation as well as treatment of metastatic disease. SPECT/CT, a relatively newer modality, has shown to play a pivotal role predominantly in the post-therapy setting by changing the risk stratification of patients with thyroid cancer. In the case of radioio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 76 publications
0
49
0
Order By: Relevance
“…Most of the orally ingested iodine is rapidly cancer by helping to determine the presence of nodal or distant metastases before radioiodine treatment. After thyroidectomy with or without lymph node dissection, radioiodine is also used for thyroid remnant ablation, for adjuvant treatment, and for the treatment of distant metastases (3)(4)(5). Posttherapy scintigraphy, which is typically performed 5-9 days after treatment, has a higher sensitivity for distant metastases than pretreatment scintigraphy because of the improved target-to-background ratio (5).…”
Section: Radioiodine Physiology and Biodistributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the orally ingested iodine is rapidly cancer by helping to determine the presence of nodal or distant metastases before radioiodine treatment. After thyroidectomy with or without lymph node dissection, radioiodine is also used for thyroid remnant ablation, for adjuvant treatment, and for the treatment of distant metastases (3)(4)(5). Posttherapy scintigraphy, which is typically performed 5-9 days after treatment, has a higher sensitivity for distant metastases than pretreatment scintigraphy because of the improved target-to-background ratio (5).…”
Section: Radioiodine Physiology and Biodistributionmentioning
confidence: 99%
“…the presence of lymph node metastasis (4). These factors are important to determine the intent of radioiodine treatment and the appropriate dose, as well as to aid interpretation of the scintigrams (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common treatment for TC without metastasis is surgery. Chemotherapy and radioactive iodine treatment are also medical treatment options in addition to surgery [3]. However, the prognosis of recurrent TC is not good with the above treatments [4].…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis of seven prospective controlled clinical trials indicated that FDG-PET under TSH stimulation either by thyroid hormone withdrawal or by rhTSH had slightly improved diagnostic performance in detecting Tg-positive and WBS-negative DTC lesions. FDG-PET/CT is useful in staging, response assessment after chemotherapy, targeted therapies, or radiotherapy and prognostic assessment for patients with cancer [55]. Therefore, PET/ CT imaging should be performed as first-line, with empiric 131 I treatment being considered only for those patients with no detectable FDG uptake [51].…”
Section: (3) 18 F-fdg-pet/ct or Pet/mrimentioning
confidence: 99%